Effect of Heat Treatment on the Mechanical Properties of Aluminium 6063 Reinforced with Alumina, Titania, and Hybrid Powders - Anuoluwapo Blessing Bello; Johnson Sunday Alabi; Ayowole Oluwaseyi Elugbaju; Olumide Joseph Olapade (ABUAD Journal of Engineering Research and Development, 2025)
The research examines the mechanical behaviour changes of alumina and titania-reinforced Aluminium 6063 composites after T6 heat treatment. The stir casting method combined with 3 wt% or 6 wt% reinforcement followed by a heat treatment solution at 520°C for 2 hours, then water quenching and artificial aging at 180°C for 8  hours. Tensile properties and hardness were enhanced through heat treatment such that peak hardness reached 116 HRB in 6 wt% TiO₂ composites. Tensile strength increased by 44.8% in 3 wt% TiO₂ composites (192.8 MPa), and peak hardness reached 116 HRB in 6 wt% TiO₂ samples. The impact strength of materials decreased with reinforcement addition, but heat treatments introduced marginal improvements when working with low reinforcement amounts. The research findings present essential knowledge to improve Aluminium 6063 composites for automotive and aerospace sector applications.